The block-grid method for the approximation of the pure second order derivatives for the solution of Laplace's equation on a staircase polygon - Dosiyev, A. A. (Elsevier, 2014)
The combined block-grid method is developed for the highly accurate approximation of the pure second order derivatives for the solution of Laplace's equation on a staircase polygon. By approximating the pure derivatives with respect to one of the variables on an artificial boundary around the reentry vertices, the approximation problem of this derivative is reduced to the solution of a special Dirichlet finite difference problem on the nonsingular part of the polygon. For the error in the maximum norm O(h(iota)), iota = 2, 4, 6 order of estimations are obtained, when the boundary functions on the boundary of the nonsingular part of the polygon are from the Holder classes C-iota+2,C-lambda , 0 < lambda < 1. Numerical experiments are illustrated to support the theoretical results. (C) 2013 Elsevier B.V. All rights reserved.
16th International Congress on Computational and Applied Mathematics (ICCAM) -- JUL 09-13, 2012 -- Ghent, BELGIUM
Keywords: Approximation of derivatives; Singularity; Artificial boundary; Block-grid method; Matching operator